Analysis of Qur'anic Interpretation of Catcalling as Gender Symbolic Violence in Muslim Public Spaces - Puspita, Mega; Yuslem, Nawir (Universitas Muhammadiyah Surakarta, 2025)
Catcalling, as a form of symbolic gender-based violence, has become a serious issue in urban public spaces, particularly within Muslim societies. This study aims to analyze the phenomenon of catcalling through a Qur'anic interpretive framework, focusing on Tafsir Al-Misbah by Quraish Shihab, to formulate educational and advocative strategies grounded in Islamic spirituality. Employing a qualitative phenomenological approach and thematic tafsir methodology, data were collected from in-depth interviews with female catcalling survivors and a textual study of relevant Qur'anic verses and prophetic traditions. The findings reveal that catcalling contradicts the principle of karāmah insāniyyah (human dignity) (Q.S. Al-Isra' [17]:70), the prohibition of talmizu (mockery) (Q.S. Al-Hujurat [49]:11), and the Qur'anic spirit of gender-equal righteous deeds (Q.S. An-Nahl [16]:97). Moreover, prophetic teachings on ethical speech serve as a moral foundation to reject verbal abuse. The study also finds that spiritual recovery grounded in Islamic values can be an effective curative approach to the psychosocial impact on victims. Preventive strategies involving maqāṣid al-syari'ah-based education and Qur'anic public campaigns have the potential to foster a culture of respectful and just communication. These findings affirm that Qur'anic interpretation, when applied contextually and practically, can serve as a transformative instrument in addressing gender-based violence. The methodology included in-depth interviews with survivors and semantic-thematic analysis of religious texts.